N6‐Methyladenosine‐Modified CBX1 Regulates Nasopharyngeal Carcinoma Progression Through Heterochromatin Formation and STAT1 Activation. Issue 36 (30th October 2022) - Zhao, Yin; Huang, Shengyan; Tan, Xirong; Long, Liufen; He, Qingmei; Liang, Xiaoyu; Bai, Jiewen; Li, Qingjie; Lin, Jiayi; Li, Yingqin; Liu, Na; Ma, Jun; et al.
Abstract: Epitranscriptomic remodeling such as N 6 ‐methyladenosine (m 6 A) modification plays a critical role in tumor development. However, little is known about the underlying mechanisms connecting m 6 A modification and nasopharyngeal carcinoma (NPC) progression. Here, CBX1 is identified, a histone methylation regulator, to be significantly upregulated with m 6 A hypomethylation in metastatic NPC tissues. The m 6 A‐modified CBX1 mRNA transcript is recognized and destabilized by the m 6 A reader YTHDF3. Furthermore, it is revealed that CBX1 promotes NPC cell migration, invasion, and proliferation through transcriptional repression of MAP7 via H3K9me3‐mediated heterochromatin formation. In addition to its oncogenic effect, CBX1 can facilitate immune evasion through IFN‐ γ ‐STAT1 signaling‐mediated PD‐L1 upregulation. Clinically, CBX1 serves as an independent predictor for unfavorable prognosis in NPC patients. The results reveal a crosstalk between epitranscriptomic and epigenetic regulation in NPC progression, and shed light on the functions of CBX1 in tumorigenesis and immunomodulation, which may provide an appealing therapeutic target in NPC. Abstract : m 6 A methylomes are mapping in nasopharyngeal carcinoma (NPC) using m 6 A sequencing, and CBX1 is identified to be significantly upregulated with m 6 A hypomethylation in metastatic NPC tissues. The functions of CBX1 in promoting NPC tumorigenesis and immune evasion are further uncovered, in which CBX1 facilitates transcriptional repression of MAP7 via H3K9me3‐mediated heterochromatin formation and activates IFN‐ γ ‐STAT1 signaling‐mediated PD‐L1 upregulation.